Impact of Highly Active Antiretroviral Therapy on the Natural History of Cervical Precancerous Lesions: A 17-Year Institutional Longitudinal Cohort Study. (July 2014) - Patrelli, Tito Silvio; Gizzo, Salvatore; Peri, Francesca; Franchi, Laura; Volpi, Lavinia; Esposito, Federica; Pedrazzi, Giuseppe; Antoni, Anna Degli; Modena, Alberto Bacchi
We performed an observational cohort study in order to assess the correlation between precancerous cervical lesions (cervical intraepithelial neoplasia [CIN]) and immunological state in human immunodeficiency virus (HIV)-positive women treated by highly active antiretroviral therapy (HAART). We analyzed 194 HIV-infected women referred to the Parma-Universitary Hospital for early detection of human papilloma virus–induced CINs. We analyzed cytology, colposcopy, and CIN degree according to HAART: group A untreated and group B treated. We compared the CD4+ count and viral load at the time of CIN onset and the time interval between diagnosis of HIV and the onset of CIN. Group A and group B showed homogeneous results for general features, CD4+ count, viral load, and Papanicolaou test features. Differences were not found in terms of histology and CD4+ value, viral load count, pharmacological treatment, years since the diagnosis of HIV, age, smoking, sexual promiscuity, previous intravenous narcotics abuse, prostitution, sexually transmitted diseases, ethnicity, and age at diagnosis. Histology and the clinical stage of HIV showed significant concordances between the high degree of cervical dysplasia and advanced stage of HIV disease.